Federal Aid Projects in Manhattan, Kansas During the Great Depression - Mundell, Julie (Kansas State University. Dept. of History, 2013)
After the stock market crash of 1929, the country fell into a deep financial depression. Devastated by losses, the citizens of the United States were eager for relief. President Franklin D. Roosevelt promised the people a “New Deal” in which he enacted a series of programs designed to relieve the pressures of financial difficulty, recover the economy from the devastating losses, and reform the stock market and financial system to discourage a repeat. New Deal programs designed by the federal government to stimulate struggling economies benefited the city of Manhattan and the Kansas State College enough for them to survive the Great Depression. Programs created jobs that ranged from clerical work to construction. By looking at the national context, programs in Manhattan and programs for students and women, we can see how the New Deal programs helped struggling cities and what the long-term effects of these programs were.
Keywords: New Deal; Great Depression; Manhattan, Kansas; Kansas State College; WPA